Assembly processes lead to divergent soil fungal communities within and among 12 forest ecosystems along a latitudinal gradient. Issue 3 (6th June 2021) - Zheng, Yong; Chen, Liang; Ji, Niu‐Niu; Wang, Yong‐Long; Gao, Cheng; Jin, Sheng‐Sheng; Hu, Hang‐Wei; Huang, Zhiqun; He, Ji‐Zheng; Guo, Liang‐Dong; Powell, Jeff R.
Summary: Latitudinal gradients provide opportunities to better understand soil fungal community assembly and its relationship with vegetation, climate, soil and ecosystem function. Understanding the mechanisms underlying community assembly is essential for predicting compositional responses to changing environments. We quantified the relative importance of stochastic and deterministic processes in structuring soil fungal communities using patterns of community dissimilarity observed within and between 12 natural forests and related these to environmental variation within and among sites. The results revealed that whole fungal communities and communities of arbuscular and ectomycorrhizal fungi consistently exhibited divergent patterns but with less divergence for ectomycorrhizal fungi at most sites. Within those forests, no clear relationships were observed between the degree of divergence within fungal and plant communities. When comparing communities at larger spatial scales, among the 12 forests, we observed distinct separation in all three fungal groups among tropical, subtropical and temperate climatic zones. Soil fungal β‐diversity patterns between forests were also greater when comparing forests exhibiting high environmental heterogeneity. Taken together, although large‐scale community turnover could be attributed to specific environmental drivers, the differences among fungal communities in soils within forests was high even at local scales.